Do fallow in the off-season and crop succession promote differences in soil aggregation in no-tillage systems? - Fernandes, Mariele Monique Honorato [UNESP]; Coelho, Anderson Prates [UNESP]; Silva, Matheus Flavio da [UNESP]; Fernandes, Carolina [UNESP] (Elsevier, 2022)
The no-tillage (NT) system is an agricultural practice that stands out the most within conservation agriculture. Conservation agriculture is based on three principles: soil tillage that is limited to the sowing row, crop rotation, and soil surface cover throughout the year (>30%). Despite these principles, the maintenance of soil cover throughout the year and crop rotation are commonly neglected, which can promote changes in soil aggregation. The aim of this study was to evaluate the effects of fallow in the off-season, and two crop successions (grass/grass and grass/legume), on soil aggregation in NT systems. The study was conducted in five fields with different land uses for more than 10 years in southeastern Brazil. Three land uses under NT, all sown with maize within the season, were used, yielding three groups: NT with fallow in the off-season (NT-f), NT with legumes (brown hemp) in the off-season (NT-l), and NT with maize in the off-season (NT-g). For comparison, we considered forest land (F) as a conservation reference for soil aggregation and land being used under conventional tillage (CT) as a low-conservation system. The soil variable that contributed the most to the separation of land use was the mineral-associated organic carbon content. The absence of soil surface cover throughout the year in an NT system is as harmful to soil aggregation as a CT system. Moreover, succession promotes differences in soil aggregation, with grass-grass succession (NT-g) leading to higher particulate organic carbon content and aggregate stability index in some soil layers compared to the NT-l. Here, we demonstrate that conservation agriculture practices, such as NT, require a system-centered approach to improve soil conditions. We also found that fallow in the off-season promotes an NT system with low soil conservation.
Keywords: Conservation systems; Conventional soil tillage system; Discriminant analysis; Organic carbon